2003
DOI: 10.1037/0090-5550.48.3.195
|View full text |Cite
|
Sign up to set email alerts
|

A conjoint analysis of factors influencing American and Taiwanese college students' preferences for people with disabilities.

Abstract: To determine the effect of demographic variables on attitudes toward disability. Participants: Eighty-three female American and 89 female Taiwanese college students. Outcome Measure: A conjoint measurement of 16 stimulus cards (representing people with varying disability labels, severity of disability, age, gender, and education). Procedures: The participants were asked to sort the stimulus cards according to their personal preferences for working with people with disabilities. Results: Younger and higher educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 34 publications
(33 reference statements)
4
29
0
Order By: Relevance
“…Recent research by Dowjotas (2009) on students' attitudes towards children with autism found that attitudes differed based on severity, such that students were most positive toward children with mild autistic symptoms and more negative toward children with more severe autistic symptoms. These results for severity were found across all measures used to assess participants' attitudes, and also seem consistent with prior research (e.g., Socall & Holtgraves, 1992;Wang, Thomas, Chan, & Cheing, 2003). The severity of the autism diagnoses with which the professionals were working in the Barnes-Holmes et al (2006) study were unspecified by the participants, and therefore it is unclear whether severity played a role in the discord between the disclosure of attitudes in the current study compared to the research by Barnes-Holmes et al Furthermore, it is worth noting that the mainstream group reported significantly greater levels of socially desirable responding relative to the ABA tutors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Recent research by Dowjotas (2009) on students' attitudes towards children with autism found that attitudes differed based on severity, such that students were most positive toward children with mild autistic symptoms and more negative toward children with more severe autistic symptoms. These results for severity were found across all measures used to assess participants' attitudes, and also seem consistent with prior research (e.g., Socall & Holtgraves, 1992;Wang, Thomas, Chan, & Cheing, 2003). The severity of the autism diagnoses with which the professionals were working in the Barnes-Holmes et al (2006) study were unspecified by the participants, and therefore it is unclear whether severity played a role in the discord between the disclosure of attitudes in the current study compared to the research by Barnes-Holmes et al Furthermore, it is worth noting that the mainstream group reported significantly greater levels of socially desirable responding relative to the ABA tutors.…”
Section: Discussionsupporting
confidence: 90%
“…These findings could be seen as contradictory to previous research, whereby individuals typically tend to be motivated to mask negative socially sensitive attitudes, thus producing a divergence between implicit and explicit measures (Barnes-Holmes et al, 2010). However, as noted above more severe diagnoses may produce more explicitly negative attitudes (Dowjotas, 2009;Wang et al, 2003). Future research exploring this issue in greater detail would be valuable.…”
Section: Discussionmentioning
confidence: 69%
“…Beyond the above conceptual explanation, the differences in stigma between the two disability groups provide support for the disability hierarchy (Miller et al, 2009;Wang et al, 2003), whereby people with ID are less socially desirable and less accepted than people with PD. Since individuals may tend to over-report positive attitudes, we can hypothesize that stigma toward people with ID is even more pronounced than was reported in this study.…”
Section: Discussionmentioning
confidence: 92%
“…Little is known about the literatures that are associated with the disability status of the observers but instead, there were some studies made on the perceptions toward people with specific types of disabilities. Wang, Thomas, Chan, and Cheing (2003) have only ranked the students' disability preference in their study and they did not study on whether one with disability or without disability would have a positive or negative perception towards people with disabilities. Whereas, Deal (2003) indicated that disability categorization is utilized by individuals with disabilities to determine their attitudes toward people with disabilities similarly with the individuals without disabilities.…”
Section: Table 3 -Studies On Attitudes Towards People With Disabilitimentioning
confidence: 99%